Prevalence of Preeclampsia in Adolescent - Ahmad, Asad; Mohammed, Shaher Bano; Sohail, Maria; Ashraf, Hafiza Sana; Safdar, Zainab; Asghar, Marya (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2020)
Adolescent pregnancy is one of the most highlighted social and public health issues present at a global level with varying prevalence rate. It represents a massive risk group in reproductive terms due to the excessive burden of growth along with reproduction. Pregnancy at such a young age may lead to premature delivery, pre-eclampsia, and massive fetal deaths. These adverse outcomes are influenced by in adequate prenatal care, poor socioeconomic status, and weight gain during pregnancy. The prevalence rate of preeclampsia is twice as higher in teenagers than any other age group of women. Objective: To know the prevalence of pre-eclampsia in adolescent pregnancy and to find out the relationship of pre-eclampsia with age group, body mass index, and education of pregnant young girls. Methods: An observational (cross-sectional) study was conducted on 383 females selected through a nonprobability convenience sampling technique. The study was conducted at Aziz Bhatti Shaheed Teaching Hospital within the duration of 5 months after approval of the synopsis. Data were analyzed by using SPSS 21.0. Chi-square and person correlation tests were used to find out the association of pre-eclampsia with age group, body mass index and education. Results: The mean age of the participants was 20±1 years. Total 383 females were chosen for the study. Results showed that n=114 (29.8%) were suffering from preeclampsia while n 269 (70.23%) were not. There was a significant relationship of pre-eclampsia. Conclusions: The prevalence is quite prominent in pregnant females showing that are at a higher risk of adverse pregnancy outcomes. However, the study also shows that the majority of women suffering from pregnancy-induced hypertension were illiterate. Therefore, health literacy is important for females to interpret and apply healthcare information for making accurate health decisions in such a critical aspect of life.